Why is technology adoption not optimised? E-commerce business investigation in Java Island - Fitriani, Novi; Setiawan, Doddy (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2023)
Technology adoption is essential to increase business competitiveness and performance. Technology can be adopted regarding sales media, payment, and shipping methods. Statistics Indonesia reports that as of June 30, 2021, businesses in Indonesia are still dominated by conventional types of business, only 25.92% of companies are conducting e-commerce activities. However, even businesses already doing e-commerce, they still use simple technology through instant messaging and social media. Technologies with more relevant features to sales, such as marketplaces and websites, are not used optimally. The low technology adoption  can also be seen from the payment method, which is still dominated by cash at 77%, and the delivery method by face-to-face at 85%. Therefore, this research investigates why e-commerce businesses in Java have not been optimal in adopting technology. This study uses raw data from the 2021 e-commerce survey conducted by Statistics Indonesia. The population in this study is all e-commerce businesses on the island of Java, totaling 1,774,589 units, with a sample of 5,543 units. The results of this study indicate that the variables of education, training, age, gender, capital, and labor issues tend to be related to technology adoption. The variable delivery service limitations tend not to be related to technology adoption.JEL Classification D31; P42; P46